2018
DOI: 10.1021/acs.accounts.8b00349
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Precise Dichalcogenolate-Protected Copper and Silver Superatomic Nanoclusters and Their Alloys

Abstract: CONSPECTUS:The chalcogenolato silver and copper superatoms are currently a topic of cutting edge research besides the extensively studied Au n (SR) m clusters. The crystal structural analysis is an indispensable tool to gain deep insights into the anatomy of these subnanometer clusters. The metal framework and spatial arrangement of the chalcogenolates around the metal core assist in unravelling the structure-property relationship and fundamental mechanistic involved in their fabrication. In this Account, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
210
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(222 citation statements)
references
References 50 publications
7
210
0
1
Order By: Relevance
“…Furthermore, DFT calculations indicate that [Ag 13 ] 5+ can be treated as an 8 e − superatomic unit (with 1S 2 1P 6 closed‐shell configuration) capped by a external shell (Figure B, right) . Many dichalcogenolated silver superatomic nanoclusters based on [Ag 21 {S 2 P(O i Pr) 2 } 12 ] + , through ligand and doping engineering, such as [Ag 21 {Se 2 P(OEt) 2 } 12 ] + , [Ag 20 {S 2 P i (OR) 2 } 12 , [Au@Ag 19 {S 2 P(OPr) 2 } 12 ], [Ag 20 {Se 2 P(O i Pr) 2 } 12 ], [AuAg 20 {Se 2 P(OR) 2 } 12 ] + , and [Au 3 Ag 18 {Se 2 P(O i Pr) 2 } 12 ] + , were obtained and summarized in detail by the group of Liu in a review on copper/silver superatomic nanoclusters . With more in‐depth research, the exploration of gold and silver nanocluster analogues has attracted attention to understand fundamental differences .…”
Section: Geometric and Electronic Structures Of Metal Superatomic Clumentioning
confidence: 99%
“…Furthermore, DFT calculations indicate that [Ag 13 ] 5+ can be treated as an 8 e − superatomic unit (with 1S 2 1P 6 closed‐shell configuration) capped by a external shell (Figure B, right) . Many dichalcogenolated silver superatomic nanoclusters based on [Ag 21 {S 2 P(O i Pr) 2 } 12 ] + , through ligand and doping engineering, such as [Ag 21 {Se 2 P(OEt) 2 } 12 ] + , [Ag 20 {S 2 P i (OR) 2 } 12 , [Au@Ag 19 {S 2 P(OPr) 2 } 12 ], [Ag 20 {Se 2 P(O i Pr) 2 } 12 ], [AuAg 20 {Se 2 P(OR) 2 } 12 ] + , and [Au 3 Ag 18 {Se 2 P(O i Pr) 2 } 12 ] + , were obtained and summarized in detail by the group of Liu in a review on copper/silver superatomic nanoclusters . With more in‐depth research, the exploration of gold and silver nanocluster analogues has attracted attention to understand fundamental differences .…”
Section: Geometric and Electronic Structures Of Metal Superatomic Clumentioning
confidence: 99%
“…Additionally, two new copper hydrides 3 and 4 were isolated and the synthesis of cluster 4 from 3 via ligand exchange method is a remarkable instance where structural anatomy was retained at utmost precision. Our synthesis of copper hydrides via ligand exchange is parallel to the synthesis of Se‐protected silver nanoparticles . This methodology is particularly useful for the supporting ligands such as Se‐donor ligands that are not stable in solution in the presence of reducing reagents.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, atomically precise gold clusters have been utilized often as promising templates for fabrication. [12] For example, the ligand exchange reactions on [Au 38 24 ] and [Au 40 24 ] (2-PET = 2-phenylethanethiolate) clusters with BINAS (BINAS=1,1 0 -binapthyl-2,2 0 -dithiol) as an incoming ligand were reported by Knoppe and coworkers. [11a] Ackerson et al reported the first single-crystal X-ray structure of a partially exchanged NC [Au 102 (p-MBA) 40 (p-BBT) 4 ] [11b] by the ligand replacement of p-MBA (para-mercaptobenzoic acid) with p-BBT (para-bromobenzene thiol) on a 5 min timescale of exchange reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] This structural feature appears to prevent the shrinkage of the clusters,which is caused by the replacement of Ag I by Cu I in the outer and inner shells due to the formation of the much shorter Cu À Sb onds compared with the Ag À Sb onds.T he replacement of all the Ag I atoms in the [Ag 4 S] 2+ core also induces the shrinkage of the clusters.T hus,t he three Ag I atoms that form shorter AgÀSb onds because of the 2coordination geometry in the [Ag 4 S] 2+ core,r ather than the remaining Ag I atom with 4-coordination geometry,u ndergo replacement by Cu I atoms in 1.T his is the first nanocluster system that shows aA g I -to-Cu I exchange at the core of the cluster structure,a lthough Liu and co-workers previously reported the insertion of Au I atoms into the center of "colloidal" silver or copper nanoclusters. [43,44] …”
Section: Discussionmentioning
confidence: 99%